An element through the looking glass: exploring the Au–C, Au–H and Au–O energy landscape. Issue 48 (20th November 2015) - Roşca, Dragoş-Adrian; Wright, Joseph A.; Bochmann, Manfred
Abstract : Gold has seen a remarkable transformation from inert noble metal to highly reactive catalyst. However, its organometallic chemistry contains many unknowns. How certain can we be about the species involved in catalytic cycles? This Perspective summarises recent discoveries. Abstract : Gold, the archetypal "noble metal", used to be considered of little interest in catalysis. It is now clear that this was a misconception, and a multitude of gold-catalysed transformations has been reported. However, one consequence of the long-held view of gold as inert metal is that its organometallic chemistry contains many "unknowns", and catalytic cycles devised to explain gold's reactivity draw largely on analogies with other transition metals. How realistic are such mechanistic assumptions? In the last few years a number of key compound classes have been discovered that can provide some answers. This Perspective attempts to summarise these developments, with particular emphasis on recently discovered gold(iii ) complexes with bonds to hydrogen, oxygen, alkenes and CO ligands.